Evaluation of anti-scorpion (Hottentota tamulus) venom potential of native plants extracts using mice model. (3rd July 2022) - Butt, Samima Asad; Tahir, Hafiz Muhammad; Ali, Shaukat; Tariq, Muniba; Hassan, Ali; Summer, Muhammad; Raza, Chand; Khan, Shafaat Yar
Abstract: Hottentota tamulus (Fabricius, 1798) (Scorpiones: Buthidae) is among the most common venomous species of scorpions in Punjab, Pakistan. The venom of this species has high risk of morbidity and mortality. Several medicinal plants have been reported to have anti-scorpion venom potential. However, there is scarcity of scientific evidences that could prove the anti-scorpion venom potential of plant extracts. The aim of present study was to evaluate the anti-venom activity of four native plants extracts, i.e. Mangifera indica L., Achyranthes aspera L., Allium cepa L. and Ginkgo biloba L. using Swiss albino mice as model. The Methanolic/aqueous extracts of plants were mixed with LD99 of Hottenota tamulus and injected intraperitoneally. The response was recorded till 7 th day of treatment. Moreover, hematological and serological analyses were performed after administration of LD50 and LD99 doses of venom. The extracts of A. aspera and A. cepa completely neutralized (100%) the effect of scorpion venom, but neutralization effect of G. biloba was comparatively less (83.3%). However, M. indica (leaves and flowers) did not neutralize the effect scorpion venom. The extracts of plants were analyzed by GC-MS for the compositional analysis. The major compounds found in A. aspera, A. cepa and G. biloba were Oleanolic acid, cyclopropane, Lupeol acetate, a cholesterol, palmitic acid and Stearic acid respectively. It is concluded that A. aspera and A. cepa completely neutralize the effect of venom and could be used in future to design anti-scorpion venom agent.